DAILY FLIGHT ACTIVITY OF BEES IN THE EXPERIMENTAL GROUPS - Nizomitdinova M. Sh. (Web of Journals Publishing, 2025)
The article examines the daily flight activity, speed, and return to the hive with pollen and nectar of Carpathian bee colonies fed with soy milk for 3 minutes during spring, summer, and autumn seasons, and draws relevant conclusions.
Keywords: Mother bee, soybean milk, flight activity, pollen, nectar, flight speed, migration.